THE EFFECTIVENESS OF STEM-BASED LEARNING IN IMPROVING STUDENTS' SCIENCE LITERACY IN TEMPERATURE AND HEAT - Nistilawati; M. Agus Satriawan (Jurnal Inovasi Fisika dan Edukasi, 2025)
Improving science literacy is one of the main focuses in 21st-century learning, especially in the context of physics learning, which requires conceptual understanding and scientific thinking skills. However, various studies show that Indonesian students' science literacy is still relatively low, particularly in the abstract subject matter of temperature and heat, which requires a contextual approach. Therefore, this study aims to determine the effectiveness of STEM-based learning (Science, Technology, Engineering, and Mathematics) in improving students' science literacy in the subject matter of temperature and heat. This study uses a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research sample consisted of two 11th grade high school classes, namely the experimental group that received STEM-based learning and the control group that received conventional learning. The instruments used were multiple-choice science literacy tests based on PISA science literacy indicators and learning implementation observation sheets. Data collection was conducted through pre-tests and post-tests on both groups. Data were analyzed descriptively and inferentially. Normality and homogeneity tests were conducted before proceeding with the independent two-sample t-test. The analysis results showed that there was a significant difference between the science literacy scores of the experimental group and the control group with a significance value (p) of 0.000 (< 0.05). The average posttest score of the experimental group was higher than that of the control group. The conclusion of this study indicates that STEM-based learning is effective in improving students' science literacy on the topic of temperature and heat. This approach integrates conceptual understanding with scientific skills through contextual and problem-solving oriented learning activities.